Preparation and Characterization of TiO2 Nanoparticles With and Without Magnetic Field Effect Via Hydrothermal Technique - Hameed, Howraa Ghassan; Abdulrahman, Nadia A. (Iraqi Journal of Science, 2023)
With and without the use of magnetic fields, titanium dioxide (TiO2) nanoparticles were synthesized using the hydrothermal method at extremely high temperatures and pressures. Titanium tetra isopropoxide [Ti(C12H28O4)] was used for the preparation, which was performed at pH 7 and under temperatures of 160 and 190 ˚C. UV spectroscopy, XRD crystallography, FE-SEM microscopy were used for characterizations. From UV spectroscopy, the energy gap values were clearly affected by the increase in temperature and the presence of the magnetic field. At the temperatures of 160 and 190 oC for TiO2 without magnetic field, FE-SEM microscopy images have shown an average crystal diameter of 13.436 and 12.551 nm, respectively. While for TiO2 with the presence of magnetic field, the crystal diameters were found to be 14.665 and 14.468 nanometers, respectively, at same temperatures. Additionally, XRD analysis has revealed that the average crystal size of TiO2 at 160 and 190 ˚C without a magnetic field is 13.13 and 11.59 nanometers, respectively. While the crystal sizes for TiO2 in the presence of a magnetic field were determined to be 13.19 and 12.93 nanometers, respectively.